2022
DOI: 10.3390/ijerph19010476
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Parenting Confidence and Later Child Mental Health in the Area Affected by the Fukushima Nuclear Disaster: The Fukushima Health Management Survey

Abstract: After the 2011 Fukushima Daiichi Nuclear Power Station accident, the Fukushima Health Management Survey was conducted to assess children’s lifestyle and mental health conditions. The participants in this study were 1126 children, aged 0 to 3 years, living in the evacuation zone at the time of the disaster. The parenting confidence of their mothers was assessed using a self-administered questionnaire as a baseline in 2013. We examined the association of parenting confidence level at baseline, using a total diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Despite these limitations, this study revealed and organized the negative experiences of self-evacuation had by mothers of small children following the FDNPS accident, which were previously unknown. Generally, both the women and children were vulnerable and easily began to struggle in their situation following the disaster [32,33]. The study indicated that these mothers who chose to evacuate to an unfamiliar region experienced highly stressful situations.…”
Section: Discussionmentioning
confidence: 97%
“…Despite these limitations, this study revealed and organized the negative experiences of self-evacuation had by mothers of small children following the FDNPS accident, which were previously unknown. Generally, both the women and children were vulnerable and easily began to struggle in their situation following the disaster [32,33]. The study indicated that these mothers who chose to evacuate to an unfamiliar region experienced highly stressful situations.…”
Section: Discussionmentioning
confidence: 97%